2009
DOI: 10.1182/blood-2008-12-193375
|View full text |Cite
|
Sign up to set email alerts
|

EBV Zta protein induces the expression of interleukin-13, promoting the proliferation of EBV-infected B cells and lymphoblastoid cell lines

Abstract: Epstein-Barr virus (EBV) infection can modify the cytokine expression profiles of host cells and determine the fate of those cells. Of note, expression of interleukin-13 (IL-13) may be detected in EBV-associated Hodgkin lymphoma and the natural killer (NK) cells of chronic active EBV-infected patients, but its bio-logic role and regulatory mechanisms are not understood. Using cytokine antibody arrays, we found that IL-13 production is induced in B cells early during EBV infection. Furthermore, the EBV lytic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 50 publications
2
82
1
Order By: Relevance
“…Interferon-␥ knockout mice infected with murine herpesvirus (MHV68) develop lung fibrosis and display elevated levels of IL-13 (58). Similar to effects of Zta on IL-13 expression in B cells (79), Zta transcriptionally activates the IL-13 gene in lung epithelial cells. IL-13 promotes collagen synthesis and fibroblast proliferation in vitro and in vivo (28,72), and IL-13 inhibition may reduce lung inflammation and remodeling (8).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Interferon-␥ knockout mice infected with murine herpesvirus (MHV68) develop lung fibrosis and display elevated levels of IL-13 (58). Similar to effects of Zta on IL-13 expression in B cells (79), Zta transcriptionally activates the IL-13 gene in lung epithelial cells. IL-13 promotes collagen synthesis and fibroblast proliferation in vitro and in vivo (28,72), and IL-13 inhibition may reduce lung inflammation and remodeling (8).…”
Section: Discussionmentioning
confidence: 75%
“…Zta also interacts with several key cellular transcriptional regulatory proteins that affect inflammation including NF-B (61), p53 (53), and the histone acetylase CREBbinding protein (2). Zta-mediated regulation of cellular genes involved in the inflammatory process such as IL-8 (27), IL-13 (79), and TGF-␤ (11,27) has also been demonstrated.…”
mentioning
confidence: 99%
“…It had been shown that Epstein-Barr Virus plays an important role in pathogenesis of HL [22][23][24] . Moreover, Tsai and colleagues 25 have determined a relationship between IL-13 and the EBV ZTA protein in both cell lines as well as EBV infected lymphoblastoid cell lines and suggested a contribution of the increased expression of IL-13 in HL's pathogenesis. Formerly, we had determined a previous EBV infection rate of approximately 90% in patients with HL and BL treated in our center 26,27 .…”
Section: Resultsmentioning
confidence: 99%
“…Transfection of DNA into cells was performed using TrasIT-LT1 Transfection Reagent (Mirus) according to the manufacturer's instructions. The methods for production and infection of lentiviruses were performed as our previous description (22). Briefly, 0.5 mg p8.91, 1 mg pMD2.G, and 1.5 mg pCMSCV vector or pCMSCV-FLAG-RUNX1b were cotransfected into 1.2 Â 10 6 HEK293T cells.…”
Section: Mutational Analysismentioning
confidence: 99%
“…After 24 hours, the cells were transfected with 0.5 mg pCR3-CBFb combined with 0.5 mg expression plasmids of either wild-type (wt)-RUNX1b, its mutants, or control vector, pcDNA, respectively. The nuclear extracts of the cells were harvested as previously described (22) and applied for electrophoretic mobility shift assay (EMSA) by using the LightShift Chemiluminescent EMSA Kit (Thermo scientific) according to the manufacturer's instructions. Briefly, both forward and reverse strands of the oligonucleotides were labeled with biotin at the 5 0 ends and annealed together to form a double strand probe.…”
Section: Electrophoretic Mobility Shift Assaymentioning
confidence: 99%